PERNIKAHAN DINI DAN IMPLIKASINYA TERHADAP KEHIDUPAN KELUARGA PADA MASYARAKAT MADURA (PERSPEKTIF HUKUM DAN GENDER) - Faridatul Jannah, Umi Sumbulah (EGALITA, 2012)
Early marriage phenomenon in Madurese society is caused by parents’worry towards their children’s behaviour, self readiness, reducing economic  burden of the family, and less awareness of the importance of education. This sort of marriage implies on child care and the way the couple educatetheir child and tension within the marriage which is ended by divorce.People’s perceptions on early marriage practice are categorized intoproponent and opponent groups. The reasons for those who disagree withthe marriage are couple’s readiness in managing the family, couple’s agematurity biologically, sociologically as well as psychologically which willinfluence family’s life. By contrast, for those who agree with this earlymarriage, they propose that this marriage is practiced to save the religion and to avoid free sex. Besides, there are some parents who are proud if their children get married soon and not to be late age girl. Economic reason isanother consideration for parents that the son in law will support themfinancially.g